Efficiency Analysis with Borrowing and Lending: Criteria and Their Effectiveness - Levy, Haim; Kroll, Yoram (The Review of Economics and Statistics, 1979)
Fama, Eugene F., and James D. MacBeth, Return and Equilibrium: Empirical Tests, Journal of Political Economy 81 (May 1973), 607-636. Jensen, Michael C., Foundations and Current State of Market Theory, in Michael C. Jensen (ed.), Studies in the Theory of Markets (New York: Praeger Publishers, 1972). Johnston, John, Econometric Methods (New York: McGraw-Hill Book Company, 1972), 345-346. Levy, Robert A., On the Short-Term Stationarity of Beta Coefficients, Financial Analysts Journal 27 (Nov. 1971), 55-62. Lintner, John, Valuation of Risk Assets and the Selection of Risky Investments in Stock Portfolios and Budgets, this REVIEW 47 (Feb. 1965), 768-775. Marshall, William J., Jess B. Yawitz, and Edward Greenberg, On the Comparative Statics of Asset Price Adjustments, working paper, Washington University Graduate School of Business, 1977. Miller, Merton H., and Myron Scholes, Rates of Return in Relation to Risk: Re-examination of Some Recent Findings, in Michael C. Jensen (ed.), Studies in the Theory of Markets (New York: Praeger Publishers, 1972). Mossin, Jan, in a Asset Market, Econometrica 34 (Oct. 1966), 768-775. Rao, Potluri, and Roger Leroy Miller, Applied Econometrics (Belmont, CA: Wadsworth Publishing Company, Inc., 1968), 204. The authors attribute the proof to A. S. Merrill, Frequency Distribution of an Index Where Both the Components Follow the Normal Law,; Biometrika 20 (1928), 53-63. Rubinstein, Mark E., A Mean-Variance Synthesis of Corporate Financial Theory, Journal of Finance 28 (Mar. 1973), 167-181. Sharpe, William F., Capital Asset Prices: Theory of Market Equilibrium Under Conditions of Risk, Journal of Finance 19 (Sept. 1964), 425-442.